Personal Learning Environments in Formative Research - Hidalgo Benites, Lilliam Enriqueta (2025)
Introduction: Formative research at the university uses didactic strategies supported by information and communication technologies (ICT) to facilitate the development of research skills. Objective: To describe a formative research experience that used Personal Learning Environments (PLEs) for the acquisition of digital research skills, as well as to identify the tools and activities involved in the construction of these environments. Method: A qualitative-quantitative research approach was applied using a documentary-descriptive design. The intentional, non-probabilistic sample consisted of 79 students who took courses in 2022 in the Faculties of Social Sciences and Education, Sciences, and Industrial Engineering at the National University of Piura. Results: A total of 39 theoretical articles were prepared in peer groups using virtual tools and activities that formed part of the PLEs. Conclusion: The combination of pedagogical strategies and technology enables the development not only of research skills but also of digital research competencies.